Performance Analysis of the Entropy Waspas Method in Determining Official Travel for Regional Revenue Agency Employees of North Sumatra Province - Nasution, Chairul Ichwan; Maulana, Halim (Cattleya Darmaya Fortuna, 2024)
This research aims to (1) find out how the process of official travel for employees of the Regional Revenue Agency of North Sumatra Province is, (2) design a decision support system for a website system in the process of implementing official travel for employees of the Regional Revenue Agency of North Sumatra Province. This research method uses quantitative research. Data analysis technique using the Entropy-Waspas Method. The sample used in the research consisted of 27 alternatives. Data collection was carried out by observation, interviews and literature study. Next, a simulation of the Waspas entropy calculation was obtained by carrying out (1) determining alternatives and (2) determining criteria. The researchers obtained the results that (1) Using the Entropy Waspas Method in the support system for determining BAPENDA employees entitled to travel on business can make it easier for BAPENDA to select employees who have the right to travel on business and (2) the system calculation results show the same results between system calculations and manual calculations seen from the highest ranking value.